Home Switch Control using Electromyograph and AVR Microcontroller - Markis, Lince; Wardana, P. Susetyo; Novi (SOTVI, 2023)
The increasingly rapid development of technology in the field of biomedical engineering, one of which is applying EMG (Electromyograph) signals to move mechanical devices. Various studies have been carried out with various methods tested. The research entitled